For Whom? Studying the Singapore Zoological Gardens, 1973–1993 - Sim, Wan Zhen (Nanyang Technological University, 2020)
For many who grew up with the Singapore Zoo, one might recall the death of its most iconic mascots such as Ah Meng and Inuka. Such animals were definitely not unique since the colonial times due to the proliferation of wildlife trafficking which carried on well after independence. By tracing the evolution of zoos and the state of natural history, this thesis will examine the “makings” of the Singapore Zoo between 1973 to 1993, exploring how it was conceptualised. This thesis argues that the meanings of zoos have always been changing to fit its historical context. Likewise, the zoo was framed to be distinctly different from the “unethical” menageries of the past, an “enlightened” institution that suited the context of a newly independent republic to portray itself as a successful emerging nation. These new meanings were also transferred onto the zoo animals; they did not merely symbolise power and entertainment anymore but rather, the education and conservation of their species. In essence, the zoo and its animals did not exist as a lone entity but were understood in relation to their function for the nation. As such, the Singapore Zoo was constructed by, and for, humans.